Eastern Europe as a Liminal Space in the Life and Fiction of Philip Roth - Bryla, Martyna Marika (My University, 2013)
In the present paper, the concept of liminality is applied to study the portrayal and significance of the post-war Eastern Europe, and Czechoslovakia in particular, in the life and fiction of one of the best contemporary American authors, Philip Roth. Liminality is an anthropological concept that refers to the transitional phase of a rite of passage. It is characterized by “ambiguity and paradox, a confusion of all customary categories” (Turner 97). At the same time, this apparent lack of structure has transformative and creative properties, and may bring about novel configurations and possibilities. The concept has gained well-deserved popularity beyond anthropology proper. Among others, it has been applied to explore theatre and literature. More recently, scholars in political and social studies have recognized its potential for studying large-scale social and political movements and transformations. Both communism and post-communism have been analysed from the perspective of liminality. Furthermore, some scholars conceptualized the condition of post-war Eastern Europe as liminal. Given liminality’s potential for illuminating the two major strands of this paper: literature and politics, I analyze the communist Prague in Philip Roth’s The Prague Orgy (1985) as a liminal space that forces the protagonist, a successful American novelist Nathan Zuckerman, to face and revise his own preconceptions of the place and himself. By sending Zuckerman behind the Iron Curtain and confronting him with the native authors whose works have been banned by the regime, Roth poses a more universal question about the nature of literature and the function of writer. Additionally, I resort to Philip Roth’s biography to explore the writer’s personal connection with “the Other Europe.” I am especially interested in the author’s travels to Czechoslovakia between 1972 and 1977, and the way they affected his personal and creative life. As this paper attempts to demonstrate, Roth’s and Zuckerman’s Czechoslovak experience is liminal in character and as such endowed with transformative and generative potential.
Keywords: Roth, Philip - Crítica e interpretación; Eastern Europe; Liminality; Philip Roth